Methodological and scientific support for student sports teams - Koroleva O.Yu. ,; Alekseeva A.A. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is aimed at confirming the effectiveness of the psychological support provided to the women's volleyball team by the coaching staff to improve the performance of the game. Methods and structure of the study. An anthropometric profile of the "typical" player of the University team and, in general, the teams participating in the first league of the Russian Championship has been created. Testing of the sports team was organized and carried out. The technique used by a psychophysiologist when working with athletes is described. A set of measures has been developed and implemented for the psychological and psychophysiological support of the team. Research results and conclusions. The use of a team approach in the training of the women's volleyball team demonstrated a clear correlation with improved results at district and national competitions. The practice of the coaching staff and a psychologist working together with a team consisting of candidates for the Master of sports has proven its effectiveness, which is confirmed by the successful performances of the university team in the 2023-2024 and 2024-2025 seasons. This conclusion is supported by comparing the performance results of this team with the achievements of teams that have undergone similar training in the same region. The data obtained can be applied to work with semi-professional volleyball teams in regions where there are no super league teams in sports schools and Olympic reserve schools.